Effect of cadmium stress on the content of phytochelatins in Salix variegata - LIU Yuan; WANG Niya; ZHANG Wen; YU Jia; WEI Hong (浙江大学学报. 农业与生命科学版, 2017)
With rapid development of industrialization and urbanization in China, large amounts of heavy metals have been directly or indirectly released into the soil environment through solid wastes, waste air, and waste water from industrial activities over the recent decades. In particular, cadmium (Cd) is one of the most toxic pollutants causing environmental problems. With excellent water solubility, Cd can be absorbed by plants easily and transferred to human body, eventually threatening the health of human beings. Lots of herb plants have tolerance for Cd and can accumulate to eliminate the Cd pollution in soils. However, with relative low biomass, the accumulation capacity of herb plants is limited. Little is known about the phytoremediation application of woody plants, which have large biomass and fast growth rate. Salix variegata has strong bioaccumulation on Cd and exceptionally high tolerance to Cd stress, especially planted along the sloping banks, thus it has the potential for phytoremediation of Cd polluted environments. However, the mechanism of tolerance and detoxification for Cd still needs further study. Metal binding ligands are effective for detoxification of heavy metals, mainly phytochelatins (PCs) and metallothioneins (MTs).In this study, in order to explore the detoxification mechanism of S. variegata, and improve the potential enrichment and detoxification ability of S. variegata, hydroponic experiments were conducted under different Cd2+ concentrations, including 0 mg/ L Cd2+ (CK), 2 mg/L Cd2+ (T1), 10 mg/L Cd2+ (T2), 20 mg/L Cd2+ (T3) and 50 mg/L Cd2+ (T4), and the Cd2+ and thiol-peptide contents in leaves and roots of S. variegata were determined.The results showed that under the Cd stress, four kinds of thiol- peptides (PC2, PC3, PC4 and PC5) were detected in the leaves, and two kinds of thiol-peptides (PC2 and PC3) were detected in the roots. The total content of thiol-peptides in the leaves and roots of S. variegata increased with the Cd concentration and treatment time. The contents of glutathione (GSH) in the leaves and roots of S. variegata under different levels of Cd stress were significantly higher than that of the control treatment. Besides, the content of thiol- peptides in the leaves of S. variegata also increased significantly than the control. The increase of thiolpeptides was proportional related to the increase of Cd concentration. Meanwhile, the PC2 and PC3 contents of the T4 group in the roots of S. variegata were significantly higher than the control. Significant positive correlations between thiol-peptide content and Cd accumulation were observed in the leaves and roots of S. variegata. Altogether, these results indicated that the thiolpeptide content increased with the Cd accumulation in the leaves and roots of S. variegata.In conclusion, with intensified Cd stress, the chelating ability of phytochelatin to Cd increased significantly, and the tolerance and the detoxification ability of S. variegata to Cd stress were substantially improved. The PC2 content of each Cd concentration treatment in the leaves and roots of S. variegata was the highest among the thiol-peptides, especially in the roots of S. variegata. Therefore, the chelating ability of PC2 to Cd in S. variegata is the best among the thiol- peptides, especially the chelating ability of PC2 to Cd in the root.